Modelling the shape and thermal dynamics of Ni superalloy rings during spray forming Part 1: Shape modelling - Droplet deposition, splashing and redeposition - Mi, J; Grant, P (2008)
A numerical model has been developed to simulate the dynamic shape evolution of Ni superalloy rings during spray forming. The model comprises: (1) a droplet primary deposition model, simulating droplet primary deposition at a deposition surface; (2) a droplet splashing model, simulating the droplet splashing/scattering behaviour; and (3) a droplet redeposition model, simulating the redeposition of the scattered droplets onto the deposition surface. The model has been validated against experiments of spray forming large diameter IN718 alloy rings, and for the first time, the effects of droplet splashing and redeposition on the dynamic shape evolution of spray forming IN718 alloy rings and the deposition yields have been investigated and quantified. The model serves as the basis for a thermal dynamic model that is described in Part 2 of this publication. © 2007 Acta Materialia Inc.